2016
DOI: 10.1109/tmtt.2016.2519027
|View full text |Cite
|
Sign up to set email alerts
|

Open-Ended Coaxial Dielectric Probe Effective Penetration Depth Determination

Abstract: We have performed a series of experiments which demonstrate the effect of open-ended coaxial diameter on the depth of penetration. We used a two layer configuration of a liquid and movable cylindrical piece of either Teflon or acrylic. The technique accurately demonstrates the depth in a sample for which a given probe diameter provides a reasonable measure of the bulk dielectric properties for a heterogeneous volume. In addition we have developed a technique for determining the effective depth for a given prob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 40 publications
(48 reference statements)
8
100
1
Order By: Relevance
“…However, recent studies [16], [17], have suggested that there is not a linear proportionality of contribution, specifically, tissues closer to the probe tip contribute to the dielectric measurement more than tissues further from the probe tip. This finding suggests that the contribution of tissues to the dielectric data is not equal to the proportion of volume occupied by those tissues in the Histology Region.…”
Section: Tissue Contribution To Dielectric Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…However, recent studies [16], [17], have suggested that there is not a linear proportionality of contribution, specifically, tissues closer to the probe tip contribute to the dielectric measurement more than tissues further from the probe tip. This finding suggests that the contribution of tissues to the dielectric data is not equal to the proportion of volume occupied by those tissues in the Histology Region.…”
Section: Tissue Contribution To Dielectric Propertiesmentioning
confidence: 99%
“…In order to examine heterogeneous tissue structures, a measurement tank was developed based on the one in [17]. Within the tank, a solid material is placed on the bottom, surrounded by a liquid.…”
Section: A Dielectric Measurement Set-upmentioning
confidence: 99%
See 2 more Smart Citations
“…The effective sensing volume of the open-ended coaxial probes for tissue measurements has been widely studied for various applications. A number of studies (Hagl et al 2003, Meaney et al 2014, Meaney et al 2016 assessed the sensing depth of the slim probe (2.2 mm diameter) for tissue measurement applications and reported minimum sample thickness of less than 2 mm for accurate measurements. The average sample size in the study presented in this paper was 20 mm (minor axes) by 25 mm (major axis).…”
Section: Sample Size and Sensing Volumementioning
confidence: 99%